Smoking and Quitting Behavior by Sexual Orientation: A Cross-Sectional Survey of Adults in England. Issue 1 (2nd March 2020) - Jackson, Sarah E; Brown, Jamie; Grabovac, Igor; Cheeseman, Hazel; Osborne, Ciaran; Shahab, Lion
Abstract: Objective: To assess associations between sexual orientation and smoking and quitting behavior among adults in England. Methods: Data were collected from 112 537 adults (≥16 years) participating in a nationally representative monthly cross-sectional survey between July 2013 and February 2019. Sexual orientation was self-reported as heterosexual, bisexual, lesbian/gay, or prefer-not-to-say. Main outcomes were smoking status, e-cigarette use, cigarettes per day, time to first cigarette, motivation to stop smoking, motives for quitting, use of cessation support, and past‐year quit attempts. Associations were analyzed separately for men and women using multivariable regression models adjusted for relevant covariates. Results: Smoking prevalence is now similar between gay (21.6%), prefer-not-to-say (20.5%) and heterosexual men (20.0%), and lesbian (18.3%) and heterosexual women (16.9%), but remains higher among bisexual men (28.2%, adjusted odds ratio [ORadj ] = 1.41, 95% confidence interval [CI] = 1.11 to 1.79) and bisexual women (29.8%, ORadj = 1.64, 95% CI = 1.33 to 2.03) and lower among prefer-not-to-say women (14.5%, ORadj = 0.85, 95% CI = 0.72 to 0.99). Among smokers, bisexuals were less addicted than heterosexuals, with bisexual men smoking fewer cigarettes per day ( B adj = −2.41, 95% CI = −4.06 to −0.75) and bisexual women less likely to start smoking within 30 min of waking (ORadj = 0.66, 95% CI = 0.45 to 0.95) than heterosexuals. However, motivation to stop smoking and quit attempts did not differ significantly. Conclusions: In England, differences in smoking prevalence among people with different sexual orientations have narrowed, primarily driven by a larger decline in smoking rates among sexual minority groups than heterosexuals. Bisexual men and women remain more likely to smoke but have lower levels of addiction while being no less likely to try to quit. Implications: This population-based study provides an up-to-date picture of smoking and quitting behavior in relation to sexual orientation among adults in England. Findings suggest that widely documented disparities in smoking prevalence have narrowed over recent years, with gay men and lesbian women no longer significantly more likely to smoke than heterosexuals, although smoking remains more common among bisexual men and women. Insights into differences in level of addiction, use of cessation support, and motives for quitting may help inform the development of targeted interventions to further reduce smoking among sexual minority groups.